A Study on Mahi Dam Water Treatment Using Alum, Carbon Activation and Membrane Filtration: Exploring Effective Water Treatment Techniques at Mahi Dam (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Water is a basic common asset. Without it, life couldn't exist and individuals couldn't endure. For over 5,000 years, dams have given individuals a dependable wellspring of the water they need to live. In our examination we will learn about the alum, membrane filtration, activated carbon filters and the water treatment process.